THE NORMAN CONQUEST OF 1066 AND ITS IMPACT ON ENGLAND - Xidirova Fayoza G’ulom qizi; Ne’matova Madina Baxtiyor qizi (TADQIQOTLAR, 2025)
Annotation:  The  Norman  Conquest  of  1066  and  Its  Impact  on  England The  Norman  Conquest  of  1066  was  one  of  the  most  significant  turning  points  in English history. When William, Duke of Normandy, defeated King Harold II at the Battle of Hastings, he became William the Conqueror — the new ruler of England. This  event  completely  transformed  the  country’s  political,  social,  and  cultural structure. The Normans introduced a new system of governance, known as feudalism, which  reorganized  land  ownership  and  strengthened  royal  power.  The  English language also changed, as many French words entered the vocabulary. Additionally, Norman  architecture,  such  as  castles  and  cathedrals,  reshaped  the  landscape  of England.  Overall,  the  Norman  Conquest  marked  the  beginning  of  a  new  era  that connected England more closely with continental Europe and laid the foundation for the modern English nation.